Efektivitas Penggunaan Media Pembelajaran Roda Putar dalam Meningkatkan Pemahaman Kosa Kata Bahasa Arab di Mts Nurul Karim NW Kebon Ayu - Baik Istinawati; Santika Santika; Syauqi Miftahul Karim; Suparmanto Suparmanto (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Mufrodat is a part of language that can’t away from language it self. Learning mufrodat for students is not as easy as it, the learning process might be boring dan just memorizing the theme that teacher was told to making student interest and students skill getting lower and lower. By using the spinning wheel media for learning Arabic language might increase skill from students. The objective this study is to know the efectivity spinning wheel media for increase the students skill at learning mufrodat Arabic language. The result from this study showed that majority of students is capable at learning mufrodat Arabic language. Spinning wheel media can be used for an alternative at learning Arabic language for increase students ability.